If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X * 2 + -12X = 2X + 7 Reorder the terms for easier multiplication: 3 * 2X + -12X = 2X + 7 Multiply 3 * 2 6X + -12X = 2X + 7 Combine like terms: 6X + -12X = -6X -6X = 2X + 7 Reorder the terms: -6X = 7 + 2X Solving -6X = 7 + 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. -6X + -2X = 7 + 2X + -2X Combine like terms: -6X + -2X = -8X -8X = 7 + 2X + -2X Combine like terms: 2X + -2X = 0 -8X = 7 + 0 -8X = 7 Divide each side by '-8'. X = -0.875 Simplifying X = -0.875
| 19+169r^2=380 | | 2.1x-2.16=0.84-5.4 | | 5w=6w-8 | | 5x+2x-6=43 | | 3(2u-3)-2(u+4)= | | 5p^2-17=28 | | f(x)=x-26 | | -400=8(-8b+6) | | 9(-39/2)-5((-39/2)-6) | | 5(w+6)-7w= | | 5x/5x^3 | | 9(-39/2)-5((-39/2)-6 | | 7v^2-3=4 | | -7x+9-4x=130 | | -10-6x+2x=-22 | | 5x^3/5x= | | 10.7w+4=57.87 | | 5p^2-1=194 | | 9+3x=2x+-6 | | -135=7x+5x-3 | | 3n+2.4=6.6 | | -(v+1)-1= | | 5y/2=40 | | 26x-8-16x+3=21x-7-11x+15 | | 6X*2+9X-6=0 | | 131=5(7+5x)+7x | | 3(n+2.5)=6.6 | | 0.142857*14= | | -2(w+3)-4(w+4)= | | 3(n+2.4)=6.6 | | 40x+(20x*1.5)=1500 | | 44+5y-19=17y-11-3y |